COVID-19 and headache - Honchar, A V; Kovalchuk, P V; Katilov, O V (Pain medicine, 2021)
Since the start of the COVID-19 pandemic scientists from all over the world have been working thoroughly to study this disease and its connections with other pathological conditions. In this review the specificity of headache in patients who had had COVID-19 infection in terms of differential diagnosis is estimated. Due to increasing amount of cases, this information will be extremely helpful for doctors who are managing such patient as well as for headache specialists.